Implementation of the Regional Spatial Plan in the Development Process of North Minahasa Regency - Nelwan, Michael C.; Masengi, Evi Elvira; Tarore, Steven Vleike (Technium Social Sciences Journal, 2025)
This research aims to find out, analyze and describe 1) Regional space utilization procedures in the development process in North Minahasa Regency; 2) Determinant factors of Regional Space Utilization Procedure in the Development Process in North Minahasa Regency. The research method used is phenomenological qualitative method. The result of this study showed that First, the implementation of the Program of the Regional Regulation of North Minahasa Regency Number 1 of 2013 concerning the Regional Spatial Plan of North Minahasa Regency Year 2013-2033 requires revision or in-depth review. The role of the relevant Technical Offices is very important in realizing development and development in accordance with the Regional Spatial Plan. Intensive socialization to the people of North Minahasa Regency about this regional regulation is needed, as well as improvement of human resources, especially the capacity of state civil apparatus in the Technical Office for Spatial Planning Implementation. Second, determinant factors affecting the implementation of the Regional Spatial Plan include the lack of revision or review of the Regional Regulation of North Minahasa Regency, as well as the lack of commitment from the local government in implementing development in accordance with the regional spatial plan. The lack of means to disseminate information on the Regional Spatial Plan is also an inhibiting factor, along with the lack of technical guidance and capacity building of state civil apparatus in the field of spatial planning. Thus, the importance of taking strategic steps to improve the effectiveness of the implementation of the Regional Spatial Plan of North Minahasa Regency, including the revision of relevant regulations, strengthening government commitment, and improving the quality and capacity of relevant human resources, is an urgency that must be immediately faced by the local government in realizing sustainable and directed development in accordance with the established plan.